"It Just Always Seemed Like it Wasn't a Big Deal, Yet I Know for Some People They Really Struggle with It": LGBT Religious Identities in Context. Issue 4 (31st January 2017) - Fuist, Todd Nicholas
Abstract : Scholarly examinations of lesbian, gay, bisexual, and transgender (LGBT) religious identities have typically focused on "identity reconciliation, " which assumes that being both LGBT and religious is a "contradiction, " and posits a "coherent" identity as a desired end goal. The present research draws on a qualitative study of three LGBT‐identified congregations to demonstrate that there are a variety of ways in which LGBT religious people approach the connection between their LGBT identity and their religion. While some participants of the study did feel a need to reconcile these aspects of their self, others report never feeling a strong conflict between their LGBT identity and faith. The differences in these understandings of LGBT identity emerge out of the sociotemporal contexts the interviewees exist in, suggesting that different contexts provide divergent resources for identity performances. Through these findings, I contribute to our understanding of the intersection of religious agency, religious identities, and religion as a quality of social spaces.